Study Some Immunological and Physiological aspects in Arthritis patients - F .Drwesh, Mayada; S.Al-wazney, Wafa; Mohammad Joda, Suaad (Al-Qadisiyah Journal of Pure Science, 2018)
The present study was designed to assess some immunological and physiological aspects of arthritis patients by studying some physiological and serological parameters for 40 cases (aged 50-70 years) from AL- Sadr Teaching Hospital in AL- Najaf City Center of arthritis and physical therapy. 40 blood samble from arthritis patients which deveded into two groups : The First group consisted of (20) patients who were have high disease severity by examined the interaction with C-Reactive Protein +ve with (20) patients who were have low disease severity by examined the interaction with C-Reactive Protein –ve. Results of all required tests were obtained from the two groups compared with that results obtained from control group which included (20) healthy volunteers. Heamatological parameters included Total count of leucocytes , Hemoglobin estimation , Packed cell volume measurement , Erythrocyte sedimentation rate measurement ,Rhumatoid factor and CReactive Protein in addition to Specific activity of Adenosine deaminase and assess level of IL-1 concentration . Statistical analysis of results revealed that there was a significant (P <0.05) increase in the total count of leukocytes, also found that there are a significant (P <0.05) increase in the Erythrocyte Sedimentation Rate in two groups when compared with the control group. Otherwise, the study exhibited significant decreased (P <0.05) in Hemoglobin concentration ,percentage of packed cell volume, Mean Corpuscle Hemoglobin in the two groups when compared with the control group. Study of immunological parameters in blood serum demonstrated that there was significant increase (P <0.05) in the specific activity of adenosine deaminase as well as level of IL-1 concentration in the two groups when compared with the control group.